2013
DOI: 10.1002/iub.1233
|View full text |Cite
|
Sign up to set email alerts
|

The double life of KLF5: Opposing roles in regulation of gene-expression, cellular function, and transformation

Abstract: The mechanisms by which cells control their growth and behavioral identities are complex and require adaptability to environmental changes. Transcription factors act as master controllers of many of these pivotal points through their ability to influence the expression of many thousands of downstream genes, and increasingly research is showing that transcription factor regulation of target genes can change in response to environmental stimuli and cell type such that their function is not prescribed but rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 114 publications
2
51
0
Order By: Relevance
“…For instance, expression of KLF5 enhances cell proliferation in untransformed cells and transformed fibroblasts, whereas KLF5 suppresses cell growth in some cancer cells (28). Recent reports disclosed that xenograft tumor growth was suppressed by the expression of wild-type KLF5 but enhanced by the expression of a deacetylated KLF5 mutant (K369R) in prostate cancer cells, suggesting that the roles of KLF5 are regulated by posttranscriptional modifications (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, expression of KLF5 enhances cell proliferation in untransformed cells and transformed fibroblasts, whereas KLF5 suppresses cell growth in some cancer cells (28). Recent reports disclosed that xenograft tumor growth was suppressed by the expression of wild-type KLF5 but enhanced by the expression of a deacetylated KLF5 mutant (K369R) in prostate cancer cells, suggesting that the roles of KLF5 are regulated by posttranscriptional modifications (53).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that prostate tumor growth is regulated through the ER␤-dependent nonclassical pathway with Krüppel-like zinc finger transcription factor 5 (KLF5) (25). KLF5 (also known as BTEB2 or IKLF) is a transcription factor that possesses both tumor-suppressing and tumor-promoting activities (26)(27)(28). Analysis of the associated pathway revealed that in the absence of E2, ER␤ induces the KLF5-mediated expression of FOXO1 and increases anoikis, thereby suppressing prostate tumor growth in mouse xenograft models.…”
mentioning
confidence: 99%
“…Plenty of HIF-1α inhibitors, including chemical inhibitors, protein and nucleic acid agents, have been studied for targeted cancer therapy (26). KLF5 is predominantly present in epithelial tissues characterized by active proliferation and exerts pleiotropic effects on the regulation of tumor progression, cell proliferation and apoptosis by binding to similar GC-rich promoter of target genes (27). In our experiments, expression of HIF-1α and KLF5 was upregulated time-dependently in A549 cells exposed to 1% O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…KLF5 is part of the Kruppel-like family of transcription factors, composed of 17 members, with diverse activities in several biological processes such as cellular proliferation, metabolism, stress response, among others (Diakiw et al, 2013;Farrugia et al, 2016). KLF5 holds stable expression throughput embryonic development in mice and is required for maintenance of pluripotency (Ema et al, 2008;Parisi and Russo, 2011).…”
Section: Kruppel-like Factor 5 (Klf5)mentioning
confidence: 99%